On the gain synthesis of dynamic and integral sliding mode controllers for quad rotorcraft trajectory tracking - Benítez, Daniel; Ortega, Jovani; Ordaz, Patricio; Espinoza, Eduardo S. (Zielona Góra: Uniwersytet Zielonogórski)
This study explores the development of two control strategies based on the sliding mode approach for quad rotorcraft trajectory tracking. A dynamic and an integral-type controller are designed to ensure that the sliding surface reaches zero within a finite time, resulting in a PD-like structure. Since this structure aids in determining the gains of robust PD controllers, it is utilized for comparative analysis. To account for uncertain dynamics and external disturbances, this work proposes an offline linear matrix inequality (LMI) algorithm that guarantees ultimate uniform stability for both sliding mode controllers.
Keywords: gain tuning; sliding mode control; linear matrix inequalities; trajectory tracking; robust control